Pengaruh Religiositas dan Literasi Terhadap Kepatuhan Masyarakat Muhammadiyah dalam Membayar Zakat pada LAZISMU Sidoarjo. - Mohammad Baihaqi; Masruchin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Zakat is one of the pillars of Islam and is obligatory for all able-bodied Muslims. The level of compliance among Muslims in paying zakat remains a challenge, especially within the Muhammadiyah community itself. This study aims to determine whether religiosity and literacy influence the compliance of the Muhammadiyah community in paying zakat to the Muhammadiyah Zakat, Infaq, and Shodaqoh Institution (Lazismu) in Sidoarjo. The quantitative research method was used in this study, using the Muhammadiyah community in the Sidoarjo region as the research population. The sample was selected based on the criteria of respondents already employed. The research instrument was a questionnaire to measure the influence of religiosity and literacy on zakat compliance. Data processing used multiple linear regression analysis with the help of SPSS software. This study found that religiosity and literacy have a positive and significant influence on the compliance of the Muhammadiyah community in paying zakat at Lazismu Sidoarjo. The higher a person's religiosity, the higher their compliance in paying zakat. Similarly, with literacy, individuals with a good understanding of the concepts, laws, and procedures for paying zakat (especially in this digital age) tend to be more compliant in paying zakat, as it can be done anywhere and anytime through various platforms provided by zakat institutions. In this study, religiosity and literacy also had a simultaneous influence, contributing significantly to zakat compliance, with a coefficient of determination (R2) of 57.3%.